Khelatisasi Ion Aluminium oleh Asam Organik Eksudat Akar Brachiaria - Hafif, B.; Sabiham, S.; Iswandi, A.; Sutandi, A.; Suyamto, Suyamto (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2010)
Aluminum toxicity is one of the major factors inhibiting plant growth in acid soils. Brachiaria grass adapt to high Al concentration. This experiment was conducted to study exudation of low molecular weight organic acids (LMWOA) activated by Al, from Brachiaria roots and its potential in chelating Al. Three Brachiaria species, i.e. B. decumbens, B. ruziziensis and B. brizantha, planted in sterile sand culture and were treated with 5 Al concentrations (0, 100, 200, 300 and 400 Î¼M). After two-month experiment, three kinds of LMWOA, i.e, malic, citric, and oxalic acids, produced by the three Brachiaria-root exudates were measured in the sand culture. The production of malic acid was higher than that of citric and oxalic acid. Those organic acids were influenced by Al concentration; the higher Al concentration the higher organic acid content would be. The organic acids were also proved to form Al-organic compounds effectively of which B. decumbens and B. brizantha were more effective in chelating Al at relatively low Al (100 Î¼M) and at relatively high Al concentration (300 Î¼M and 400 Î¼M), respectively.